CFD analysis of hydrogen gas behaviour in a multi-zone flow system: a parametric study - Kumar R., Ramesh; H. C., Yogeesha; Naik N., Channa Keshava; Bhattacherjee, Abhishek; Bhowmik, Abhijit; Pawar, Mayur Dondiram; Algburi, Sameer; Mohammed, Salah Jasim; Majdi, Hasan Shakir; Khan, Sher Afghan (Semarak Ilmu Publishing, 2025)
The ANSYS CFD analysis made use of hydrogen in this study. The investigation aims at understanding the behaviour of hydrogen gas in such interactions with the inlet air and other fluid zones around it. Such research took advantage of sophisticated simulation tools to offer useful insights into gas flow and mixing patterns, thereby justifying why hydrogen could possibly become an alternative fuel one day (hydrogen is future-oriented). In addition, a model was created to establish the interaction between combustion involving hydrogen as well as tanks of inlet air. This was done on volumes for such tanks. Many factors affect performance and efficiency for different operational conditions of hydrogen gas that were explored through elaborate simulations. These findings should improve our comprehension about physics involved which plays an important role in enhancement of systems using hydrogen for power generation and also help various industries' operations using this element in their processes. It is research that looks at the complicated flow structures and behaviours that arise in fluid domains to uncover key parameters for better designs and more efficient hydrogen systems. Consequently, it is expected that the present study will help future designs of hydrogen technology so that they play a part of sustainable energy source